ANALISIS BRAND IMAGE TERHADAP JUMLAH PEMINAT PADA UNIVERSITAS MUHAMMADIYAH MAKASSAR - Astrini, Astrini; Ismail, Irnawati (Perpustakaan dan Penerbitan Unismuh Makassar, 2015)
This study aims to determine the relationship between Brand Image (Product Image) to the number of enthusiasts in the University of Muhammadiyah This study uses literature research methods and field research in which researchers spread the questionnaire (questionnaire) to the respondents ie students UNISMUH the population amounted to 20,767, while samples taken is 80 people using Cluster sampling method. the results of the questionnaire data were analyzed using quantitative analysis method and simple regression analysis. Before the data are analyzed, validity test is required, and reliability test using SPSS program. To test the hypothesis used F test (simultaneous) and T test (partial). The result of this research is Brand Variable Image Influence to Variable Interest this can be seen from the result of hypothesis prove that revealed t value = 4,437 with significance value 0,000 <0,05, Ho is rejected and H1 accepted, real (Significant) Variable Brand Image (X) to the Interests variable (Y)